Epidemiology of osteoporosis. - Holroyd, C; Cooper, C; Dennison, E (2008)
Osteoporosis represents a major public health problem through its association with fragility fractures. All osteoporotic fractures increase patient morbidity; however, fractures of the hip and vertebrae are also linked with significant mortality. The public health burden of osteoporotic fracture is likely to rise in future generations, due in part to an increase in life expectancy. Understanding the epidemiology of this disease is therefore essential in trying to develop strategies to help reduce this load. This chapter will review the epidemiology of osteoporosis, including the relationship between low bone mass and fracture. It will review the epidemiology of fractures, concentrating on the sites where the majority of age-related fractures occur. Finally it will discuss new developments in the assessment of fracture risk.